Effect of 6-months of physical exercise on the nitrate/nitrite levels in hypertensive postmenopausal women - Moraes Camila; Bacci Mauricio; Pires Carla; Zaros Pedro R; Zanesco Angelina (BMC, 2009)
Abstract Background Evidences have showed that the incidence of arterial hypertension is greater in postmenopausal women as compared to premenopausal. Physical inactivity has been implicated as a major contributor to weight gain and abdominal obesity in postmenopausal women and the incidence of cardiovascular disease increases dramatically after menopause. Additionally, more women than men die each year of coronary heart disease and are twice as likely as men to die within the first year after a heart attack. A healthy lifestyle has been strongly associated with the regular physical activity and evidences have shown that physically active subjects have more longevity with reduction of morbidity and mortality. Nitric oxide (NO) produced by endothelial cells has been implicated in this beneficial effect with improvement of vascular relaxing and reduction in blood pressure in both laboratory animals and human. Although the effect of exercise training in the human cardiovascular system has been largely studied, the majority of these studies were predominantly conducted in men or young volunteers. Therefore, the aim of this work was to investigate the effects of 6 months of dynamic exercise training (ET) on blood pressure and plasma nitrate/nitrite concentration (NOx-) in hypertensive postmenopausal women. Methods Eleven volunteers were submitted to the ET consisting in 3 days a week, each session of 60 minutes during 6 months at moderate intensity (50% of heart rate reserve). Anthropometric parameters, blood pressure, NOx- concentration were measured at initial time and after ET. Results A significant reduction in both systolic and diastolic blood pressure values was seen after ET which was accompanied by markedly increase of NOx- levels (basal: 10 ± 0.9; ET: 16 ± 2 μM). Total cholesterol was significantly reduced (basal: 220 ± 38 and ET: 178 ± 22 mg/dl), whereas triglycerides levels were not modified after ET (basal: 141 ± 89 and ET: 147 ± 8 mg/dl). Conclusion Our study shows that changing in lifestyle promotes reduction of arterial pressure which was accompanied by increase in nitrite/nitrate concentration. Therefore, 6-months of exercise training are an important approach in management arterial hypertension and play a protective effect in postmenopausal women.